Gender-based Violence in mothers who attend College at Western Headquarters-UCR, during the period from 2011-2012 - Piñeiro Ruiz, Doris (2019)
This article is the result of a qualitative research, with the purpose to analyze the types of violence by gender that Students as mothers face in different scenarios, such as family, educational and relationship context, and some empowerment strategies that they must assume to be able to fulfill their right to higher education. On these less visible, more accepted and less questioned types of violence is what we are going to reflect on, more specifically: In the physical, psychological, sexual, economic, and institutional violence experienced by the Students as mothers, in the family, relationship, and institutional context. To this end, we worked with a population of eight students who are also mothers that received the services of the University Children's House of the Western Headquarters (CIUSO), of the University of Costa Rica, during the period 2011-2012. Hence, it was considered important to bring up a topic that was being made invisible and absent in previous researches conducted by the area of Social Sciences, at this University Headquarters. For this research the qualitative approach was used, because it was of vital importance in the process of gathering and analyzing the information, by using this method it was possible to understand the different empowerment strategies, both individually and collectively that the mothers that attend college developed to face these issues of violence and be able to start or resume their higher education.The results obtained showed the presence of gender violence in its different manifestations by which means it was possible to determine that the population under study had a strong presence of social and political empowerment, due to the fact that there was a mixture of individual capacities, talent and willpower in each one of them and it was thanks to those personal attributes that collective efforts were achieved.